Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 17 1929 1,230 1937 1,413 1930 1,912 1938 1,791 1931 2,649 1939 1,514 1932 2,743 1940 963 1933 2,521 1941 350 1934 2,159 1942 123 1935 2,037 1943 92 1936 1,755 1944 (April) 75 With an economic system permanently incapable of absorbing labour into expanding industries, it was no longer logical to regard unemployment as a temporary misfortune to be insured against. Nevertheless, the contributory principle was never abandoned. The present rates in the general scheme are:—* Males. Females. Aged 22 but under 65 10d. 9d. Aged 18 but under 21 9d. 8d. Aged 16 but under 18 5d. 4½d. Under 16 2d. 2d. And the weekly rates of benefit are as follows:—† 1938 1943 s. d. s. d. Single adult man 17 0 20 0 Married adult without children 27 0 30 0 Married adult with 1 child 30 0 34 0 Married adult with 2 children 33 0 37 0 Married adult with 3 children 36 0 40 0 According to Sir John Orr, a diet adequate for health could be purchased in peacetime for less than 10/- a week. Yet child allowances, even now, are only 4/- each for the first two dependent children and 3/- for any subsequent children. Sir William Beveridge estimates that a family of four must have an income of 48/6 to keep above subsistence level. Under the unemployment insurance scheme they would get 33/- ; and the more children they had the deeper would be their poverty. (3) The Assistance Board. Until 1934, those whose period of benefit under the unemployment insurance scheme had expired, were assisted under the transitional payments scheme, administered with varying benefits by local authorities. The burden on rates in depressed areas was thus intolerable. "Unemployed persons in representative towns varied between under 3 per cent. in Coventry and Reading and 10 per cent. in Sunderland, 12 per cent. in Oldham and 18 per cent. in Llanelly, of the total population."‡ The Assistance Board § was formed to take over the administration, with central funds and uniform rates of benefit, working through its area officers and teams of investigators. The Board has since assumed three other functions : (1) It may grant assistance to people who have become impoverished owing to the war, either through changing habitation in accordance with government * Social Security, page 114. Rates are less in the Agricultural Scheme. † Facts for Socialists, page 25. ‡ Facts for Socialists, page 24. § Originally called the Unemployment Assistance Board. 15X/2/98/13